2021
DOI: 10.1002/nbm.4643
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial blood flow is the dominant factor influencing cardiac magnetic resonance adenosine stress T2

Abstract: Stress imaging identifies ischemic myocardium by comparing hemodynamics during rest and hyperemic stress. Hyperemia affects multiple hemodynamic parameters in myocardium, including myocardial blood flow (MBF), myocardial blood volume (MBV), and venous blood oxygen levels (PvO2). Cardiac T2 is sensitive to these changes and therefore is a promising non‐contrast option for stress imaging; however, the impact of individual hemodynamic factors on T2 is poorly understood, making the connection from altered T2 to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…However, this is in line with previous results and discussion around the lower sensitivity of stress T1 mapping to hemodynamic changes when compared to T2. 10) Initial results demonstrated a significant potential for the dynamic assessment of myocardial perfusion by stress T1 mapping. 27) However, conflicting results and potential T1 mapping sequence differences have shown that stress T1 mapping may provide a better assessment of myocardial blood volume instead of dynamic myocardial blood flow, 5) 6) and that stress T2 mapping is more sensitive to changes in myocardial blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is in line with previous results and discussion around the lower sensitivity of stress T1 mapping to hemodynamic changes when compared to T2. 10) Initial results demonstrated a significant potential for the dynamic assessment of myocardial perfusion by stress T1 mapping. 27) However, conflicting results and potential T1 mapping sequence differences have shown that stress T1 mapping may provide a better assessment of myocardial blood volume instead of dynamic myocardial blood flow, 5) 6) and that stress T2 mapping is more sensitive to changes in myocardial blood flow.…”
Section: Discussionmentioning
confidence: 99%
“… 27) However, conflicting results and potential T1 mapping sequence differences have shown that stress T1 mapping may provide a better assessment of myocardial blood volume instead of dynamic myocardial blood flow, 5) 6) and that stress T2 mapping is more sensitive to changes in myocardial blood flow. 10) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pig models are an important part of both translational and imaging research., e.g., to assess post-infarction inflammation using fluorine-19 MRI ( 91 ), to understand functional and microstructural changes ( 92 ) or myocardial strain ( 93 ) following acute myocardial infarction, to understand pulmonary vasomotor control and ROS in exercising swine with multiple comorbidities ( 94 ), in resuscitation research ( 12 , 95 ), to better understand imaging contrast such as the influence of myocardial blood flow on T2 ( 96 ), to develop medical devices, and as basis for computational modelling of the heart ( 7 , 97 100 ).…”
Section: Discussionmentioning
confidence: 99%